Catch-up growth and associated factors in very low birth weight infants - Teodoro Durá-Travé; Isabel San Martín-García; Fidel Gallinas-Victoriano; María Jesús Chueca-Guindulain; Sara Berrade-Zubiri (Elsevier, 2020)
Introduction: The characteristics of catch-up growth in very low birth weight infants (VLBW) have not been clearly established. The aim of this study was to analyse the height catch-up and some associated factors in a cohort of VLBW birth weight <1,500 g from birth to age 14 years. Methods: We obtained retrospective data on weight and height at birth and ages one, 2, 3, 4, 6, 8, 10, 12 and 14 years in a cohort of 170 VLBW. We compared these anthropometric values with those documented in a control group. Results: Thirty-seven children (21.8%) were born with an extremely low birth weight and 32 (18.8%) extremely preterm. At 10 years of age, 7% of VLBW (1,000-1,500 g) and 35% of extremely low birth weight <1,500 g children had short stature P = 0.001). Almost all VLBW children who had a normal height at ages 2, 4 and 10 years had exhibited adequate weight catch-up in previous evaluations. We found that extremely low birth weight and extremely preterm were independent predictors for inadequate height catch-up. Conclusion: The growth pattern of VLBW children has specific characteristics. The catch-up in weight seems to be an important factor for catch-up in height, and therefore a thorough nutritional follow-up is recommended in these children. Resumen: Introducción: Las características del crecimiento recuperador en niños con muy bajo peso (MBP) al nacer no se han establecido con claridad. El objetivo del estudio fue analizar el crecimiento recuperador de talla y factores asociados en una cohorte de niños con MBP al nacer (< 1.500 g) desde el nacimiento hasta los 14 años de edad. Métodos: Se recogieron datos retrospectivos de peso y talla a uno, 2, 3, 4, 6, 8, 10, 12 y 14 años de edad en una cohorte de 170 recién nacidos con MBP. Se compararon estos datos antropométricos con los registrados en un grupo de control. Resultados: Treinta y siete niños (21.8%) nacieron con extremado bajo peso y 32 (18.8%) fueron pretérmino extremo. A los 10 años de edad, el 7% de los niños con MBP (1.000-1.500 g) y el 35% de los niños con extremado bajo peso < 1.500 g tenían talla baja p = 0,001. Casi todos los niños con MBP que tenían una talla normal a los 2, 4 y 10 años de edad habían alcanzado un peso adecuado en evaluaciones previas. El extremado bajo peso al nacer y el nacimiento pretérmino extremo resultaron ser predictores independientes de un crecimiento recuperador de talla inadecuado. Conclusión: El patrón de crecimiento de niños con MBP al nacer tiene unas características específicas. El crecimiento recuperador de peso parece ser un factor importante para el crecimiento recuperador de talla, por lo que se recomienda un seguimiento nutricional cuidadoso en estos niños.